2021
DOI: 10.3390/ijerph18052234
|View full text |Cite
|
Sign up to set email alerts
|

Do Observed Teaching Behaviors Relate to Students’ Engagement in Physical Education?

Abstract: Teachers’ behaviors can affect students’ engagement in the Physical Education (PE) setting. According to self-determination theory, teachers can rely on either a need-supportive or a controlling teaching behavior, and these behaviors will differently affect students’ outcomes. The main objective of this research was to analyse how teaching behaviors and some contextual variables influence students’ engagement in PE classes. The present study adds to the existing literature through an observation-based design i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 61 publications
4
21
0
Order By: Relevance
“…Iconomescu et al [19] discovered that students in Romania had negative attitudes regarding the topic due to teachers' ineffective communication skills. Consistent with the available data, we can speculate that teachers can influence their students' views forward into Physical Education, which in turn can reduce students' interest and engagement in school [20,21,22]. Multiple studies have demonstrated that students' perspectives might be influenced by the variety of physical and sporting activities they are exposed to in school [23,24,25].…”
supporting
confidence: 80%
“…Iconomescu et al [19] discovered that students in Romania had negative attitudes regarding the topic due to teachers' ineffective communication skills. Consistent with the available data, we can speculate that teachers can influence their students' views forward into Physical Education, which in turn can reduce students' interest and engagement in school [20,21,22]. Multiple studies have demonstrated that students' perspectives might be influenced by the variety of physical and sporting activities they are exposed to in school [23,24,25].…”
supporting
confidence: 80%
“…Both autonomy support and involvement, but not structure, were found to contribute to Chinese college students' satisfaction of three basic psychological needs, which supported the findings in the research of Lietaert et al (2015). However, these findings were not in line with the results of research, which has revealed that the influence of teachers' structure can be positive (Tucker et al, 2002;Taylor and Ntoumanis, 2007;De Naeghel et al, 2014), or conversely, negative (Hornstra et al, 2020;González-Peño et al, 2021) Taylor and Ntoumanis, 2007), while our work was based on the experiences of Chinese college students. Compared with students in primary and high schools, university students have more opportunities to make choices in their learning programs, courses, and schedules (Ratelle et al, 2007).…”
Section: The Sdt-motivation Sequence Among Chinese College Studentsmentioning
confidence: 82%
“…Except for the positive effects of autonomy support and involvement, teacher-reported structure negatively predicted students' assessed need satisfaction in school (Hornstra et al, 2020 ). Observed teachers' structure before PE activity could negatively predict students' engagement (González-Peño et al, 2021 ); whereas students' reported structure in a Dutch language class failed to predict student engagement being measured by student, teacher, and observer (Lietaert et al, 2015 ). Thus, the current study would assist to clarify the combined contributions of perceived teachers' autonomy support, structure, and involvement to the motivational process of students.…”
Section: Sdt-based Motivational Researchmentioning
confidence: 99%
“…As well, students will be engaged when they establish social connections and improve the communication with both peers and teacher, which satisfies the need for relatedness [70]. Using an observational methodology, a recent work suggested that structure during activity and relatedness support could positively predict student engagement [10]. The results of the present study align with this finding given that, as mentioned earlier, the SEM seems to be a valid tool to enhance structure during activities as well as to support relatedness within the PE setting.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, and highlighting the importance of the PE setting, behavioral engagement has been pointed out by different authors as a key concept to predict students' learning and performance achievement [8], by suggesting a positive consequence of the type of interactions that take place between teachers and students [9]. There is evidence that the behavioral engagement displayed by students in PE can be affected by their motivational processes [10,11].…”
Section: Introduction 1behavioral Engagement In Physical Educationmentioning
confidence: 95%